2006
DOI: 10.1002/jbm.a.30933
|View full text |Cite
|
Sign up to set email alerts
|

Conjugation of extracellular matrix proteins to basal lamina analogs enhances keratinocyte attachment

Abstract: The dermal-epidermal junction of skin contains extracellular matrix proteins that are involved in initiating and controlling keratinocyte signaling events such as attachment, proliferation, and terminal differentiation. To characterize the relationship between extracellular matrix proteins and keratinocyte attachment, a biomimetic design approach was used to precisely tailor the surface of basal lamina analogs with biochemistries that emulate the native biochemical composition found at the dermal-epidermal jun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
26
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(27 citation statements)
references
References 36 publications
1
26
0
Order By: Relevance
“…29 A collagen-glycosaminoglycan (GAG) coprecipitate containing collagen (5 mg/mL) and GAG (0.18 mg/mL) was prepared. 30 The collagen-GAG coprecipitate was placed into an aluminum weigh boat, lyophilized, and crosslinked using thermal dehydration at 105°C in a vacuum of < 200 mtorr for 48 h. The collagen-GAG sponges were cut into rectangles approximately 7 cm 2 (2.5-cm width · 3-cm length) and placed in a desiccator until use.…”
Section: Production Of Ldermsmentioning
confidence: 99%
See 1 more Smart Citation
“…29 A collagen-glycosaminoglycan (GAG) coprecipitate containing collagen (5 mg/mL) and GAG (0.18 mg/mL) was prepared. 30 The collagen-GAG coprecipitate was placed into an aluminum weigh boat, lyophilized, and crosslinked using thermal dehydration at 105°C in a vacuum of < 200 mtorr for 48 h. The collagen-GAG sponges were cut into rectangles approximately 7 cm 2 (2.5-cm width · 3-cm length) and placed in a desiccator until use.…”
Section: Production Of Ldermsmentioning
confidence: 99%
“…30,32 Neonatal foreskins were obtained from nonidentifiable discarded tissues from the UMass Memorial Medical Center, Worcester, MA, and were approved with an exempt status from the New England Institutional Review Board. After 5 days of culture, NHKs were detached using 0.05% Trypsin-EDTA (Invitrogen), and passage 2-3 NHKs from multiple donors were used in all experiments.…”
Section: Culture Of Ldermsmentioning
confidence: 99%
“…5-mm and 50-mm spacings) ( Table 1) based on previously reported results, which demonstrated that channels of these sizes enhanced re-epithelialization and recapitulated the texture of the native epidermal-dermal junction. 17,36 Various aspect ratios (i.e. ratio of topography height to topography width) were tested to optimize micropattern height for guiding cell migration.…”
Section: Sample Fabricationmentioning
confidence: 99%
“…[10][11][12][13][30][31][32] If not applied appropriately, DHT crosslinking is well known to change the chemical composition of collagen-based membranes.…”
mentioning
confidence: 99%
“…12,13,30 Any cytotoxicity of strongly crosslinked, collagen-based materials could modify cell shape and significantly reduce cell growth. 31 DHT crosslinking has also been postulated to significantly decrease the rate of cell migration by masking the integrin binding sites that promote cellular attachment.…”
mentioning
confidence: 99%